KAJIAN KONDISI SOSIAL EKONOMI MIGRAN MADURA MASUK DI KELURAHAN TANAH KALI KEDINDING KECAMATAN KENJERAN KOTA SURABAYA - OKSA RIYANTA, RIDZAL; , MURTEDJO (Swara Bhumi, 2019)
AbstractTanah Kali Kedinding village is one areas in Kenjeran District, from the data on incoming migrationthe village has a total of 1460 Madura migrations. The number of incoming migrants is influenced by variousfaktors not only from migrants origin area and destination area. Therefore, the researcher was interested to findout The Study of The Socio- Economic Condition of Incoming Madura Migrant In Tanah Kali KedindingVillage of Kenjeran Dirstrict. This study was aimed (1) to find out the socio-economic condition of incomingMadura migrant in Tanah Kali Kedinding Sub-District of Kenjeran District Surabaya, (2) to know the factorsinfluenced Madura migrant in Tanah Kali Kedinding Sub-District of Kenjeran District of Surabaya.This type of reseaerch is a survey by observing and collecting facts based on variables and it presentedin the form of quantitative descriptive. The sampling used in determining respondents of this study was randomsampling, it is taking the sample randomly, the calculation of sample quantity used Slovin formula so thesample was 94, while the method to determine respondents as quantitative descriptive analysis technique withpercentages.Based on this study, the result indicated that the socio-economic of Madura Migrants in Tanah KaliKedinding Sub-Dirstrict of Kenjeran District of Surabaya were dominated by the age between 25-29 or as muchas 24.47% of 23 respondents, the gender was dominated men with 43 or 45.74% respondents, the largest maitalstatus was married ith the number 67 or 71.27% out of 94 respondents, the migrants education level wasdominated by Senior high School migrant with the total of 32.98% or 31 out of 94 respondent.Keywords : Social Condition, Economic Condition, Madura Migrant.